Impacto da presença de atrazina na comunidade bacteriana do solo - Godoi, Isamara (2012)
Chemical contamination removal in soil and water depends on microbiological community that is able to degrade these compounds. There is a great evolutionary interest on studying microorganisms that metabolize the xenobiotic ones, since they have relatively been seen as new in the last five decades. Little is known about structure variation of microbiological community of soil due do the absence and presence of s-triazine herbicides.Unlike crop dependent methods that require time to detect bacteria, molecular techniques have been developed to identify individual species in mixed populations under natural enviromments. Fluorescence in situ Hibiridization (FISH) technique overcomes some difficulties that are found out in other molecular techniques, as it does not need DNA isolation and amplification steps and allows the identification of specific genes in intact cells. Thus, this study aimed at comparing the absence/presence of atrazine effect on bacteriological community structure in soil according to the phylogenetic aspect. Target probes were used on subdivisions of alpha, beta and gamma Proteobacteria, gram-positive bacteria with high G+C content, ammonia oxidizing bacteria, nitrite oxidizing bacteria and Planctomycetes. It was also used an AtzB1 specific probe to check the atzB gene presence, which makes part of s-triazine degradation. Bacteriological amount was determined by direct counting on epifluorescence microscopy, while the corresponding values to each probe were expressed in percentages of the total count with DAPI for each sample. According to this study, positive cells were found out for all probes used in both soils, but the abundance of all groups was lower in soil contaminated with atrazine herbicide, thereby demonstrating its negative influence. Planctomycetes was the most affected group with 57% lower abundance in contaminated soil. The nitrite oxidizing bacteria was the second most affected group followed by β-Proteobacteria. It was also detected the gene atzB presence, so, it can be inferred that there are potentially degrading s-triazine bacteria in both soils.